Dynamic three‐dimensional morphogenesis of intrahepatic bile ducts in mouse liver development - Takashima, Yasuo; Terada, Maiko; Kawabata, Masuyo; Suzuki, Atsushi (Hepatology (Baltimore, Md.), 2015)
During liver development, biliary epithelial cells differentiated from bipotential hepatic progenitor cells (hepatoblasts) form a cell layer, called the ductal plate surrounding portal veins (PVs), and develop into intrahepatic bile ducts (IBDs) following developmental programs. Because IBDs make duct structures in the liver, it is necessary to perform sequential and three‐dimensional (3D) analyses from the early stages of liver development to address the process of morphogenesis in detail. However, to date, the development of IBDs has mainly been investigated using tissue sections in two‐dimensional planes, and examinations of the 3D morphogenesis and quantitative analyses based on morphometrics have not been performed. Therefore, in this study, we simulated the solid structures of IBDs from mouse embryos to adults in silico, analyzed the subjects for the length and number of developing duct structures, number of predicted connections, and discrete distance from the PV, and examined the developmental process of the IBD in detail in a quantitative manner. Conclusions: Through quantitative analyses with spatiotemporal observations using a 3D structural reconstruction model and morphometrics, we succeeded in constructing a 3D dynamic model of bile duct formation. Because the 3D reconstruction technique used in this study is available for analyzing solid structures in tissues that are difficult to approach, it shows promise for wide use in the fields of biology and medicine. (Hepatology 2015;61:1003–1011)